Method for preparing porous ceramic by photocuring sol-modified SiC particles
By sol-modifying the SiC particles to form a SiO2 film layer, and combining photocuring technology to prepare porous SiC ceramics, the problem of photocuring printing of dark-colored ceramics is solved, and the preparation of complex structure porous SiC ceramics and the manufacturing of high-score SiC/Al composite materials are realized.
Patent Information
- Application Number
- CN202411886574.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The prior art is difficult to effectively prepare photocuring 3D printing technology for dark-colored ceramics such as SiC, which makes it difficult to uniformly cure printing and achieve deep curing thickness, limiting the preparation of porous SiC ceramics and the manufacturing of complex structures of high-score SiC/Al composite materials.
By sol modification of SiC particles, SiC particles wrapped in SiO2 film layer are formed, and porous SiC ceramics are prepared in combination with photocuring technology. The method includes sol modification of SiC particles, preparation of photocured SiC slurry, photocuring 3D printing and degreasing oxidation sintering and other steps.
It significantly improves the photocuring printability of SiC ceramic particles, can design porous SiC ceramics with complex structures as required, meet the aluminized requirements, and improves the photocuring printing quality of SiC dark ceramics and the preparation efficiency of complex structures with high-score SiC/Al composite materials.
Smart Images

Figure CN119638483A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additive manufacturing and ceramic material preparation, and specifically relates to a method for manufacturing porous SiC ceramics by combining sol-modified SiC particles with photocuring additives. Background Art
[0002] Porous materials can achieve a variety of functional properties due to their unique pore structure and are called porous functional materials. They have excellent chemical stability and thermal stability, and show wide application potential in the fields of filtration materials, catalyst carriers, thermal insulation materials and biofunctional materials, especially in high-tech fields such as aerospace, biomedicine and environmental protection. Among them, porous SiC ceramics have shown wide application value in aerospace, nuclear power and transportation due to their low density, low thermal expansion coefficient, high hardness and excellent anti-oxidation properties, and have become a research hotspot in materials science. In particular, metal infiltration technology based on porous SiC ceramic materials has also been used to manufacture high-performance SiC / metal composites, among which SiC / Al composites have shown excellent performance in lightweight, high-rigidity, shock-absorbing and other components. However, with the upgrading of the application demand of SiC / Al composites, the preparation technology of porous SiC has also begun to develop towards more complex shapes and structures and lower economic costs.
[0003] Photocuring additive manufacturing technology provides a good technical guarantee for the preparation of SiC skeletons with complex structures due to its high precision, high efficiency and low cost. However, the mature ceramic material systems that can be used for photocuring 3D printing are mainly concentrated on white ceramic particles, including alumina, silicon oxide, zirconium dioxide, silicon nitride, etc., while SiC is a dark-colored ceramic. Dark-colored ceramics have strong ultraviolet light absorption ability and a refractive index mismatch with the resin, which makes it difficult to evenly cure and achieve a deeper curing thickness when printing dark-colored ceramics, limiting the development of photocuring 3D printing of dark-colored ceramics. Therefore, it is urgent to develop photocuring printing technology for dark-colored ceramic particles such as SiC to meet the preparation technology of SiC ceramic skeletons with complex structures, and then serve the preparation of porous SiC ceramics and subsequent metal infiltration needs. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing porous SiC ceramics by sol modification combined with photocuring in view of the deficiencies in the above-mentioned prior art. The method has simple steps, reasonable design and is easy to operate. SiC particles are treated with sol to prepare SiC particles wrapped with SiO2 film layer, and the modified SiC particles are used to prepare photocurable ceramic slurry to print SiC ceramic blanks, and then a complex structure porous SiC ceramic with reasonable porosity and pore size that is conducive to the infiltration of metals such as Al is prepared by designing a reasonable degreasing and sintering process, so as to accelerate the research and development process of dark-colored ceramic photocuring printing and complex structure high-score SiC / Al composite materials.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing porous ceramics by photocuring of sol-modified SiC particles, comprising the following steps:
[0006] S1. Sol modification of SiC particles
[0007] The SiC particles are ultrasonically cleaned with anhydrous ethanol to remove surface impurities and then dried, and then added to premixed liquid B, and then premixed liquid A is added to obtain a reaction mixture, the reaction mixture is stirred at 25° C. under a closed condition for 9 to 16 hours, the surface of the SiC particles is sol-modified, and the modified SiC particles are obtained after centrifugation, washing and drying;
[0008] The premixed liquid A is prepared by mixing ethyl orthosilicate and anhydrous ethanol a; the premixed liquid B is prepared by mixing deionized water, ammonia water and anhydrous ethanol b;
[0009] The mass ratio of the raw materials in the reaction mixture is: 0.5-1.0 parts of SiC particles, 3-5 parts of tetraethyl orthosilicate, 6-12 parts of anhydrous ethanol a, 4-6 parts of deionized water, 0.5-4 parts of ammonia water, and 4-20 parts of anhydrous ethanol b; the concentration of the ammonia water is 0.5-1.75 mol / L;
[0010] S2. Preparation of photocurable SiC slurry
[0011] The modified SiC particles obtained in S1 and a premixed solution of a photocurable resin are prepared into a photocurable SiC slurry, wherein a dispersant, a photoinitiator and an ultraviolet light absorber are further added to the photocurable SiC slurry;
[0012] The mass ratio of the modified SiC particles to the photocurable resin premix is 1:1:(5.5-6.5);
[0013] S3, light-cured SiC body
[0014] The photocurable SiC slurry obtained in S2 is subjected to photocurable 3D printing and, after drying, a photocurable SiC blank is obtained;
[0015] S4. Degreasing and oxidation sintering of light-cured SiC blank
[0016] The light-cured SiC body obtained in S3 was subjected to degreasing and oxidation sintering treatments, and then cooled to room temperature, ultrasonically cleaned and dried to obtain porous SiC ceramics.
[0017] Preferably, the SiC particles in S1 are spherical particles with a particle size of 10 to 165 μm and a purity of ≥99.5%.
[0018] Preferably, the drying conditions of the SiC particles after sol modification in S1 are: drying at a temperature of 80 to 120° C. for 2 to 8 hours.
[0019] Preferably, a layer of SiO2 film is attached to the surface of the SiC particles modified by the sol in S1, the thickness of the SiO2 film layer is 500-1000 nm, and the coverage rate on the SiC surface is greater than 97%.
[0020] Preferably, the amount of the dispersant added in S2 is 1% to 5% of the mass of the photocurable resin premix; the amount of the photoinitiator added is 5% to 10% of the mass of the photocurable resin premix; and the amount of the ultraviolet light absorber added is 0.5% to 1% of the mass of the photocurable resin premix.
[0021] Preferably, the preparation method of the photocurable SiC slurry described in S2 is: adding a photoinitiator and an ultraviolet light absorber to a photocurable resin premix, stirring at 25°C for 30 to 60 minutes to obtain slurry 1; adding half the mass of the modified SiC particles and half the mass of the dispersant to slurry 1, stirring at 25°C for 30 to 60 minutes and then ball milling for 6 to 8 hours to obtain slurry 2; adding the other half the mass of the modified SiC particles and the other half the mass of the dispersant to slurry 2, stirring at 25°C for 30 to 60 minutes and then ball milling for 6 to 8 hours, and after vacuum exhaust treatment, obtaining a photocurable dark SiC slurry.
[0022] Preferably, the light curing conditions in S3 are: light curing 3D printing under ultraviolet light with a wavelength of 405 nm, and the cured thickness of each layer is 50 to 200 μm; the drying conditions are: heating to 120 to 150° C. at a heating rate of 0.2 to 0.6° C. / min and drying for 1 to 2 hours.
[0023] Preferably, an integrated degreasing and sintering process is adopted in S4, and degreasing and oxidative sintering are achieved in one furnace, the atmosphere is air, and the method is: under dry conditions, the light-cured SiC blank is placed in a muffle furnace, and the temperature is increased to 650-700°C at a rate of 0.1-0.5°C / min, and kept warm for 0.5-2h; the oxidative sintering conditions are: the degreased SiC blank is heated to 1300-1400°C in a muffle furnace at a rate of 10-40°C / min, and kept warm for 0.2-3h.
[0024] Preferably, the drying temperature in S4 is 80-120° C. and the drying time is 2-6 hours.
[0025] Preferably, the porous SiC ceramic in S4 has isotropic, uniform and interconnected pores, and a porosity of 45-55%.
[0026] The present invention has the following significant technical effects:
[0027] 1. The present invention provides a method for preparing porous ceramics by photocuring of sol-modified SiC particles. The photocuring printability of SiC ceramic particles is improved by sol modification, and the macroscopic shape, microscopic pores and SiO2 film thickness of porous SiC ceramics with complex structures can be designed as required, which can well meet the requirements of aluminizing, and is expected to be applied and promoted in the fields of photocuring printing of SiC dark ceramics and manufacturing of complex structure high-score SiC / Al composite materials.
[0028] 2. The present invention forms a SiO2 film layer on the surface of SiC particles through sol modification, which significantly improves the surface state of SiC ceramic particles and makes them more compatible with the photocuring forming process, thereby obtaining a more uniform and stable quality SiC porous ceramic. The SiC porous ceramic is used to prepare a high-score SiC / Al composite material, avoiding the direct contact between Al and SiC in the subsequent infiltration process, which leads to the formation of harmful phase Al4C3. The process is simple, the parameters are controllable, and it is stable and reliable.
[0029] 3. This application innovatively proposes a simultaneous processing process of photocuring forming SiC green body and degreasing oxidation sintering, which can not only shorten the sample preparation cycle and reduce sample damage during transportation, but also significantly improve the quality and surface structure of porous SiC ceramics; the prepared porous SiC ceramics have good permeability and a continuous three-dimensional pore structure, and the pore structure and size are suitable for the flow and complete filling of aluminum and other melts.
[0030] 4. The process of this application is simple, reliable, easy to implement, and the raw materials used are low-cost. The technical principles and methods can be extended to the preparation of any high-score ceramic-metal composite materials, and even the preparation of high-melting-point metal-low-melting-point composite metal materials, and have broad guiding significance; the preparation of photocurable SiC slurry can be used to guide the slurry design for photocurable 3D printing of dark ceramic particles; the degreasing and sintering process does not require special gas protection, and can be used to guide the degreasing and sintering process design based on photocuring additive manufacturing blanks.
[0031] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The morphology of the SiC particle sol with an average particle size of 10 μm in Example 1 before and after modification, (a) before modification, (b) after modification;
[0033] Figure 2 The morphology of the SiC particle sol with an average particle size of 90 μm in Example 1 before and after modification is shown in the figure (a): before modification, (b): after modification, (c): Figure 2 (b) The enlarged view of the red box;
[0034] Figure 3 is a schematic diagram of the degreasing and oxidation sintering process of Example 1;
[0035] Figure 4 The SiC blank printed by photocuring in Example 1;
[0036] Figure 5 The porous SiC ceramic of Example 1;
[0037] Figure 6 is a microscopic morphology of the composite material after porous SiC ceramic infiltration with aluminum in Example 1;
[0038] Figure 7 This is the X-ray diffraction (XRD) diagram of the composite material after porous SiC ceramic infiltration with aluminum in Example 1. DETAILED DESCRIPTION
[0039] Example 1
[0040] This embodiment is a method for preparing porous ceramics by photocuring of sol-modified SiC particles, comprising the following steps:
[0041] S1. Sol modification of SiC particles
[0042] The SiC particles were ultrasonically cleaned with anhydrous ethanol at a power of 180 W for 30 minutes to remove surface impurities, and then dried at 120° C. for 2 hours. The dried SiC particles were added to premixed liquid B, and then premixed liquid A was added to obtain a reaction mixture. The reaction mixture was stirred at 25° C. and sealed for 9 hours. The surface of the SiC particles was sol-modified. After completion, it was centrifuged at 2000 r / min, washed with deionized water for 4 times, and dried at 120° C. for 2 hours to obtain modified SiC particles. The modified SiC surface may also contain a small amount of unattached SiO2 particles.
[0043] Wherein, the premixed liquid A is prepared by mixing ethyl orthosilicate and anhydrous ethanol a; the premixed liquid B is prepared by mixing deionized water, ammonia water and anhydrous ethanol b;
[0044] The mass ratio of the raw materials in the reaction mixture is: 0.7 parts of SiC particles, 3.2 parts of tetraethyl orthosilicate, 9.2 parts of anhydrous ethanol a, 4.8 parts of deionized water, 3 parts of ammonia water, and 7.6 parts of anhydrous ethanol b; wherein the SiC particles include two types with an average particle size of 10 μm and 90 μm, the ratio of the average particle size of 10 μm to the average particle size of 90 μm is 3:7, the purity is ≥99.5%, and the concentration of the ammonia water is 1.5 mol / L.
[0045] S2. Preparation of photocurable SiC slurry
[0046] The composition of the photocurable SiC slurry is as follows: the mass ratio of the modified SiC particles obtained in S1 to the photocurable resin premix is 11:6, the dispersant is 1.5% of the mass of the photocurable resin premix, the photoinitiator is 5.5% of the mass of the photocurable resin premix, and the ultraviolet light absorber is 0.5% of the mass of the photocurable resin premix. Among them, the photocurable resin premix is the purchased Fansike rigid resin (101S1), the ultraviolet light absorber is UV-770, the photoinitiator is (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide, and the dispersant is an oily thickener (J0602).
[0047] The preparation method is as follows: add a photoinitiator and an ultraviolet light absorber to a photocurable resin premix, stir at 25°C for 30 minutes to obtain slurry 1; add half the mass of the modified SiC particles and half the mass of the dispersant to slurry 1, stir at 25°C for 30 minutes, and then ball mill for 6 hours to obtain slurry 2; add the other half the mass of the modified SiC particles and the other half the mass of the dispersant to slurry 2, stir at 25°C for 30 minutes, and then ball mill for 6 hours, and obtain a photocurable dark SiC slurry after vacuum exhaust treatment.
[0048] S3, light-cured SiC body
[0049] The photocurable dark SiC slurry obtained in S2 was applied to a glass slide of a photocuring 3D printer and exposed to a UV surface light source with a wavelength of 405 nm for curing for 10 seconds. The uncured slurry was then cleaned off and the single layer thickness was measured to be 160 μm using a spiral micrometer. The SiC blank was then printed layer by layer to obtain a formed SiC blank with a size of 5 mm × 5 mm × 50 mm. The obtained SiC blank was then placed in a blast drying oven, heated to 120°C at a heating rate of 0.4°C / min and dried for 2 hours to obtain a photocured SiC blank.
[0050] S4. Degreasing and oxidation sintering of light-cured SiC blank
[0051] Under dry conditions, the photocured SiC blank obtained by S3 was placed in a muffle furnace, and the temperature was increased from room temperature to 650°C at a rate of 0.5°C / min and kept at this temperature for 1 hour; then the temperature was increased to 1350°C at a rate of 20°C / min and kept at this temperature for 1 hour; after that, it was cooled to room temperature, ultrasonically cleaned with deionized water for 30 minutes, and then dried at 120°C for 2 hours to obtain porous SiC ceramics.
[0052] Figure 1 The surface morphology of the original SiC particles with an average particle size of 10 μm and the SiC particles after sol treatment is shown. It can be seen that the SiO2 layer is successfully grown on the surface of the SiC particles after sol treatment, and the originally sharp surface of the SiC particles becomes blunt. Figure 2 The surface morphology of the original SiC particles with an average particle size of 90 μm and the SiC particles after sol treatment is shown, which also shows that the SiO2 layer is successfully formed on the surface of the SiC particles after sol modification. In this embodiment, the average thickness of the SiO2 layer formed on the surface of the SiC particles after sol modification is 830 nm, and the coverage rate on the SiC surface is 99%.
[0053] Figure 3 It is a schematic diagram of the debinding and oxidation sintering process. The debinding oxidation sintering is divided into two stages: the debinding stage and the oxidation sintering stage. The debinding stage is to increase the temperature from room temperature to T1=550~700℃, and the heating rate is V1=0.1~0.5℃ / min, which cannot exceed 0.5℃ / min. Exceeding it will cause interlayer separation or cracking and breakage of the SiC blank. The temperature is kept at T1 for t1=0.5~2h to ensure sufficient resin removal; the oxidation sintering temperature is T2=1300~1400℃, the heating rate from T1 to T2 is V2=10~40℃ / min, and the holding time at T2 is t2=0.2~3h.
[0054] Figure 4 It is a SiC blank printed by photocuring.
[0055] Figure 5It is a porous SiC ceramic and its structure diagram, with a porosity of 47.3%, an average pore size of 12.8μm, and a standard sample flexural strength of 1.7MPa.
[0056] The porous SiC ceramic skeleton prepared in this embodiment was subjected to aluminum infiltration treatment. The infiltration process was vacuum pressure infiltration, the infiltration alloy was ZL102 alloy, the infiltration pressure was 8 MPa, the infiltration temperature was 800°C, and the microscopic morphology of the SiC / composite material obtained after the infiltration treatment was as shown in FIG. Figure 6 As shown in the figure, no obvious impermeability phenomenon was observed. At the same time, the X-ray diffraction (XRD) results showed that no diffraction peak of Al4C3 was observed ( Figure 7 ), the flexural strength of the standard size sample of SiC / composite material after aluminum infiltration is ~423MPa, and the elastic modulus is ~176GPa, which has good comprehensive mechanical properties.
[0057] Example 2
[0058] This embodiment is a method for preparing porous ceramics by photocuring of sol-modified SiC particles, comprising the following steps:
[0059] S1. Sol modification of SiC particles
[0060] The SiC particles were ultrasonically cleaned with anhydrous ethanol at a power of 180 W for 30 minutes to remove surface impurities, and then dried at 120° C. for 2 hours. The dried SiC particles were slowly added to the premixed liquid B, and then the premixed liquid A was quickly added to obtain a reaction mixture. The reaction mixture was stirred at 25° C. and sealed for 16 hours. The surface of the SiC particles was sol-modified. After completion, it was centrifuged at 2000 r / min, washed with anhydrous ethanol for 3 times, and dried at 80° C. for 8 hours. Then, the unattached SiO2 particles were removed by sieving to obtain SiC particles with a surface covered with a SiO2 layer, which were the modified SiC particles.
[0061] The premixed liquid A is prepared by mixing ethyl orthosilicate and anhydrous ethanol a; the premixed liquid B is prepared by mixing deionized water, ammonia water and anhydrous ethanol b.
[0062] The mass ratio of the raw materials in the reaction mixture is: 0.7 parts of SiC particles, 3.2 parts of tetraethyl orthosilicate, 10.46 parts of anhydrous ethanol a, 4.8 parts of deionized water, 3 parts of ammonia water, and 18 parts of anhydrous ethanol b; wherein the SiC particles include two types with an average particle size of 10 μm and 90 μm, the ratio of the average particle size of 10 μm to the average particle size of 90 μm is 4:6, the purity is ≥99.5%, and the concentration of the ammonia water is 1 mol / L.
[0063] S2. Preparation of photocurable SiC slurry
[0064] The composition of the photocurable SiC slurry is as follows: the mass ratio of the modified SiC particles obtained in S1 to the photocurable resin premix is 11:6.5, the dispersant is 3% of the mass of the photocurable resin premix, the photoinitiator is 8% of the mass of the photocurable resin premix, and the ultraviolet light absorber is 1% of the mass of the photocurable resin premix. Among them, the photocurable resin premix is the purchased Fansike rigid resin (101S1), the ultraviolet light absorber is UV-770, the photoinitiator is (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide, and the dispersant is an oily thickener (J0602).
[0065] The preparation method is as follows: add a photoinitiator and an ultraviolet light absorber to a photocurable resin premix, stir at 25°C for 60 minutes to obtain slurry 1; add half the mass of the modified SiC particles and half the mass of the dispersant to slurry 1, stir at 25°C for 60 minutes and then ball mill for 7 hours to obtain slurry 2; add the other half the mass of the modified SiC particles and the other half the mass of the dispersant to slurry 2, stir at 25°C for 60 minutes and then ball mill for 7 hours, and obtain a photocurable dark SiC slurry after vacuum exhaust treatment.
[0066] S3, light-cured SiC body
[0067] The photocurable dark SiC slurry obtained in S2 was applied to a glass slide of a photocuring 3D printer and exposed to a UV surface light source with a wavelength of 405 nm for curing for 8 seconds. The uncured slurry was cleaned off, and the single layer thickness was measured to be 140 μm using a spiral micrometer. Then, it was printed layer by layer to obtain a formed SiC blank with a size of 5 mm×5 mm×50 mm. The obtained SiC blank was then placed in a blast drying oven, heated to 150°C at a heating rate of 0.6°C / min and dried for 1 hour to obtain a photocured SiC blank.
[0068] S4. Degreasing and oxidation sintering of light-cured SiC blank
[0069] Under dry conditions, the photocured SiC blank obtained by S3 was placed in a muffle furnace, and the temperature was increased from room temperature to 650°C at a rate of 0.3°C / min and kept at this temperature for 2 hours; then the temperature was increased to 1400°C at a rate of 40°C / min and kept at this temperature for 1 hour; after that, it was cooled to room temperature, ultrasonically cleaned with anhydrous ethanol for 20 minutes, and then dried at 100°C for 4 hours to obtain porous SiC ceramics.
[0070] In this embodiment, the average thickness of the SiO2 layer formed on the surface of the SiC particles after sol modification is 660 nm, and the coverage rate on the SiC surface is 99%.
[0071] The porous SiC ceramic prepared in this embodiment has a porosity of 52.4%, an average pore size of 14.1 μm, and a standard sample flexural strength of 1.85 MPa.
[0072] The flexural strength of the standard size sample of the SiC / composite material obtained by the aluminizing process in Example 1 is ∼412 MPa and the elastic modulus is ∼171 GPa.
[0073] Example 3
[0074] This embodiment is a method for preparing porous ceramics by photocuring of sol-modified SiC particles, comprising the following steps:
[0075] S1. Sol modification of SiC particles
[0076] The SiC particles were ultrasonically cleaned with anhydrous ethanol at a power of 180 W for 30 minutes to remove surface impurities, and then dried at 120° C. for 2 hours. The dried SiC particles were slowly added to the premixed liquid B, and then the premixed liquid A was quickly added to obtain a reaction mixture. The reaction mixture was stirred at 25° C. and sealed for 12 hours. The surface of the SiC particles was sol-modified. After completion, it was centrifuged at 2000 r / min, washed with anhydrous ethanol for 3 times, and dried at 100° C. for 5 hours to obtain modified SiC particles.
[0077] The premixed liquid A is prepared by mixing ethyl orthosilicate and anhydrous ethanol a; the premixed liquid B is prepared by mixing deionized water, ammonia water and anhydrous ethanol b.
[0078] The mass ratio of the raw materials in the reaction mixture is: 1 part of SiC particles, 5 parts of tetraethyl orthosilicate, 8 parts of anhydrous ethanol a, 4 parts of deionized water, 2 parts of ammonia water, and 5.5 parts of anhydrous ethanol b; wherein the SiC particles include three types with average particle sizes of 10 μm, 90 μm and 165 μm, the ratio is 3:7:1, and the purity is ≥99.5%, and the concentration of the ammonia water is 1.75 mol / L.
[0079] S2. Preparation of photocurable SiC slurry
[0080] The composition of the photocurable SiC slurry is as follows: the mass ratio of the modified SiC particles obtained in S1 to the photocurable resin premix is 11:5.5, the dispersant is 1% of the mass of the photocurable resin premix, the photoinitiator is 10% of the mass of the photocurable resin premix, and the ultraviolet light absorber is 0.8% of the mass of the photocurable resin premix. Among them, the photocurable resin premix is the purchased Fansike rigid resin (101S1), the ultraviolet light absorber is UV-770, the photoinitiator is (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide, and the dispersant is an oily thickener (J0602).
[0081] The preparation method is as follows: add a photoinitiator and an ultraviolet light absorber to a photocurable resin premix, stir at 25°C for 45 minutes to obtain slurry 1; add half the mass of the modified SiC particles and half the mass of the dispersant to slurry 1, stir at 25°C for 45 minutes, and then ball mill for 8 hours to obtain slurry 2; add the other half the mass of the modified SiC particles and the other half the mass of the dispersant to slurry 2, stir at 25°C for 45 minutes, and then ball mill for 8 hours, and obtain a photocurable dark SiC slurry after vacuum exhaust treatment.
[0082] S3, light-cured SiC body
[0083] The photocurable dark SiC slurry obtained in S2 was applied to a glass slide of a photocuring 3D printer and exposed to a UV surface light source with a wavelength of 405 nm for curing for 15 seconds. The uncured slurry was then cleaned off and the single layer thickness was measured to be 200 μm using a spiral micrometer. The SiC blank was then printed layer by layer to obtain a formed SiC blank with a size of 5 mm × 5 mm × 50 mm. The obtained SiC blank was then placed in a blast drying oven, heated to 135°C at a heating rate of 0.3°C / min and dried for 1.5 hours to obtain a photocured SiC blank.
[0084] S4. Degreasing and oxidation sintering of light-cured SiC blank
[0085] Under dry conditions, the photocured SiC blank obtained by S3 was placed in a muffle furnace, and the temperature was increased from room temperature to 700°C at a rate of 0.4°C / min, and kept warm for 0.5h; then the temperature was increased to 1300°C at a rate of 30°C / min, and kept warm for 3h; after that, it was cooled to room temperature, ultrasonically cleaned with anhydrous ethanol for 20min, and then dried at 80°C for 6h to obtain porous SiC ceramics.
[0086] In this embodiment, the average thickness of the SiO2 layer formed on the surface of the SiC particles after sol modification is 910 nm, and the coverage rate on the SiC surface is 98.3%.
[0087] The porous SiC ceramic prepared in this embodiment has a porosity of 51.8%, an average pore size of 15.8 μm, and a standard sample flexural strength of 1.78 MPa.
[0088] The standard size sample of SiC / composite material obtained by the aluminizing process in Example 1 has a bending strength of 417 MPa and an elastic modulus of 174 GPa.
[0089] Comparative Example 1
[0090] This comparative example uses the SiC particles and slurry ratio described in Example 1 to prepare SiC particle slurry, except that the SiC particles in this comparative example are not treated with sol. After the slurry in this comparative example is exposed to a 405nm ultraviolet light source for 10 seconds, the uncured slurry is cleaned off, and the cured thickness is measured by a spiral micrometer to be only 90μm. This indicates that the SiC particles treated with sol can significantly increase the single-layer cured thickness during photocuring printing.
[0091] The method for preparing porous ceramics by photocuring of sol-modified SiC particles of the present invention can design the macroscopic shape and microscopic pores and the thickness of the SiO2 film layer of the porous SiC ceramics with complex structures according to the requirements, and can well meet the requirements of aluminization, and is expected to be applied and promoted in the fields of photocuring printing of SiC dark ceramics and manufacturing of complex structure high-score SiC / Al composite materials. The technical principle and method of the present invention can be extended to the preparation of any high-score ceramic-metal composite material, and even the preparation of high-melting-point metal-low-melting-point composite metal materials, and has a wide range of guiding significance.
[0092] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing porous ceramics by photocuring of sol-modified SiC particles, characterized in that: The following steps are involved: S1. Sol modification of SiC particles The SiC particles are ultrasonically cleaned with anhydrous ethanol to remove surface impurities and then dried, and then added to premixed liquid B, and then premixed liquid A is added to obtain a reaction mixture, the reaction mixture is stirred at 25° C. under a closed condition for 9 to 16 hours, the surface of the SiC particles is sol-modified, and the modified SiC particles are obtained after centrifugation, washing and drying; The premixed liquid A is prepared by mixing ethyl orthosilicate and anhydrous ethanol a; the premixed liquid B is prepared by mixing deionized water, ammonia water and anhydrous ethanol b; The mass ratio of the raw materials in the reaction mixture is: 0.5-1.0 parts of SiC particles, 3-5 parts of tetraethyl orthosilicate, 6-12 parts of anhydrous ethanol a, 4-6 parts of deionized water, 0.5-4 parts of ammonia water, and 4-20 parts of anhydrous ethanol b; the concentration of the ammonia water is 0.5-1.75 mol / L; S2. Preparation of photocurable SiC slurry The modified SiC particles obtained in S1 and a premixed solution of a photocurable resin are prepared into a photocurable SiC slurry, wherein a dispersant, a photoinitiator and an ultraviolet light absorber are further added to the photocurable SiC slurry; The mass ratio of the modified SiC particles to the photocurable resin premix is 1:1:(5.5-6.5); S3, light-cured SiC body The photocurable SiC slurry obtained in S2 is subjected to photocurable 3D printing and, after drying, a photocurable SiC blank is obtained; S4. Degreasing and oxidation sintering of light-cured SiC blank The light-cured SiC body obtained in S3 was subjected to degreasing and oxidation sintering treatments, and then cooled to room temperature, ultrasonically cleaned and dried to obtain porous SiC ceramics.
2. The method according to claim 1, characterized in that: The SiC particles described in S1 are spherical particles with a particle size of 10 to 165 μm and a purity of ≥99.5%.
3. The method according to claim 1, characterized in that The drying conditions of the SiC particles after sol modification in S1 are: drying at a temperature of 80 to 120° C. for 2 to 8 hours.
4. The method according to claim 1, characterized in that: A layer of SiO2 film is attached to the surface of the SiC particles modified by the sol in S1. The thickness of the SiO2 film layer is 500-1000 nm, and the coverage rate on the SiC surface is greater than 97%.
5. The method according to claim 1, characterized in that The amount of the dispersant added in S2 is 1% to 5% of the mass of the photocurable resin premix; the amount of the photoinitiator added is 5% to 10% of the mass of the photocurable resin premix; and the amount of the ultraviolet light absorber added is 0.5% to 1% of the mass of the photocurable resin premix.
6. The method according to claim 1, characterized in that The preparation method of the photocurable SiC slurry described in S2 is as follows: adding a photoinitiator and an ultraviolet light absorber to a photocurable resin premix, stirring at 25°C for 30 to 60 minutes to obtain slurry 1; adding half the mass of the modified SiC particles and half the mass of the dispersant to slurry 1, stirring at 25°C for 30 to 60 minutes, and then ball milling for 6 to 8 hours to obtain slurry 2; adding the other half the mass of the modified SiC particles and the other half the mass of the dispersant to slurry 2, stirring at 25°C for 30 to 60 minutes, and then ball milling for 6 to 8 hours, and after vacuum exhaust treatment, obtaining a photocurable dark SiC slurry.
7. The method according to claim 1, characterized in that The light curing conditions described in S3 are: light curing 3D printing under ultraviolet light with a wavelength of 405nm, and the cured thickness of each layer is 50-200μm; the drying conditions are: heating to 120-150℃ at a heating rate of 0.2-0.6℃ / min and drying for 1-2h.
8. The method according to claim 1, characterized in that S4 adopts an integrated degreasing and sintering process, and degreasing and oxidation sintering are achieved in one furnace. The atmosphere is air. The method is: under dry conditions, the light-cured SiC blank is placed in a muffle furnace, and the temperature is increased to 650-700°C at a rate of 0.1-0.5°C / min, and the temperature is kept for 0.5-2h; the oxidation sintering conditions are: the degreasing SiC blank is heated to 1300-1400°C in a muffle furnace at a rate of 10-40°C / min, and the temperature is kept for 0.2-3h.
9. The method according to claim 1, characterized in that: The drying temperature in S4 is 80-120° C. and the drying time is 2-6 hours.
10. The method according to claim 1, characterized in that The porous SiC ceramics described in S4 have isotropic, uniform and interconnected pores, and the porosity is 45-55%.
Citation Information
Patent Citations
Composite ceramic powder and ceramic forming method
CN107540379A
Silicon carbide ceramic paste for photocuring and preparation method thereof
CN110451985A
Photo-cured silicon carbide ceramic slurry as well as preparation method and application thereof
CN114436658A
High-precision photocurable printing silicon carbide ceramic slurry, preparation method thereof and method for preparing silicon carbide ceramic product
CN117209281A
Photocuring 3D printing ceramic-polymer slurry based on aluminum sol coating method and preparation method thereof
CN118878331A